The Potential of Adsorption Technology for Batik Wastewater Treatment: A Review - Handayani, Widhi; Suwarno, Djoko; Widianarko, Budi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
The Indonesian batik plays a crucial role in supporting the country's economy. However, its production often leads to environmental problems. As sustainable development implies the need for economic benefits equally accessible by all people without compromising the environment for the future of the next generation, the sustainability of batik means that batik, as a cultural product, should be preserved, and its production can bring economic benefits without harming the environment. Therefore, environmental issues related to batik should be overcome. Studies addressing the problem of batik wastewater have been conducted; however, adsorption technology is gaining popularity due to the benefits it offers. This review examines the characteristics of batik wastewater, identifies existing batik wastewater treatment technologies, and evaluates the potential of adsorption technology for batik wastewater treatment. This literature review was conducted using Science Direct and Directory of Open Access Journals (DOAJ) search engines, which initially collected 78 articles, and finally, 58 articles were found to be suitable for the review. An Excel-based matrix was then created to analyze the literature manually. It is found that batik wastewater is usually alkaline; the Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solids (TSS) usually exceed the quality standard regulated by the Indonesian government, and are usually non-biodegradable, as indicated by the low BOD/COD ratio. Adsorption is widely applied, economically feasible, and can be easily operated by batik entrepreneurs. The performance of this technology is best when combined with other processes.